A resolução de problemas e a modelização matemática no processo de ensino - aprendizagem - avaliação: uma contribuição para a formação continuada do professor de matemática - Huaman Huanca, Roger Ruben [UNESP] (2014)
The present work consists of the materialization of an investigation that involved methodological, pedagogical and social aspects, developed in continuing education for teachers who teach Mathematics in basic education. Thomas A. Romberg’s methodology was chosen as the scientific methodology for the development of the present research. The main goal of the present work is to educate Mathematics teachers of basic education from the region of Cariri Paraibano in order that they become multipliers to the teachers from that region, focusing on capacitating them and favoring them moments of reflection and analysis about what and how to teach when they use the Methodology of Teaching-Learning- Evaluation through Problem Solving. So, a teaching-learning project was created to meet the requirements of the “5ª Gerência Regional de Ensino da Secretaria de Estado da Educação da Paraíba” and of a graduate course to the community of UEPB Campus Monteiro. The theoretical foundation considered for the development of the present research was structured on three grounds: collaborative group study in teacher continuing education; problem solving and; Mathematics modelization. That project was applied to a group of six teachers, who were selected in individual interviews, for four months, in twelve eight-hour meetings. Besides, the researcher provided daily assistance to those teachers. The methodological procedures to collect data were: interviews, observation of group work, teachers’ written material, filming, recording and field diary. The material worked by those teachers in that investigative process was simultaneously applied by the teachers who participated in that group in their own classrooms. We believe this research might contribute with Mathematics Education in order to promote a new way of working Mathematics teaching-learning in classroom